Polyunsaturated fatty acid–derived lipid mediator patterns determine viral pneumonia severity and risk for critical COVID-19 - Maria Papadaki; Eleftherios Pavlos; Marc Dubourdeau; Vincent Bailif; Kamal Badirou; Clémence A. Gély; Ioanna-Evdokia Galani; Dimitris Papelis; Natalia Kamperi; Vasiliki Triantafyllia; Eleni Siouti; Maria Salagianni; et al. (Proceedings of the National Academy of Sciences, 2026)
Severe respiratory infections such as COVID-19 are characterized by excessive inflammation leading to the development of pneumonia and acute respiratory distress syndrome. Bioactive lipid mediators (LMs) derived from ω6 and ω3 polyunsaturated fatty acids are central to the regulation of inflammation, controlling both its initiation and resolution. Still, their role in viral infections remains underexplored. By employing a holistic approach involving the analysis of white blood cell transcriptomes, targeted lipidomics, cytokine and immune cell profiling, we now show that LM patterns around hospital admission are profoundly altered in COVID-19, correlate with inflammatory responses, and stratify patients according to disease severity. Central to this are CYP450-derived LMs, such as 20-HETE, and lipoxygenase- or nonenzymatic-associated LMs such as 15-HETE, both exhibiting vasoactive function, along with lipid peroxidation metabolites such as 10-HDOHE. Among them, increased 20-HETE appears to be a promising prognostic biomarker for ICU admission and a potential therapeutic target for severe COVID-19 disease. Our study emphasizes the importance of LM patterns in COVID-19 pathophysiology and sheds light into the broader immune mechanisms beyond cytokines driving viral pneumonia in humans.